Populus gamblei Dode - a Tree New to Nagaland, India - Naithani, H. B.; Deorani, S. C.; Abenba Yaden, T. (Indian Forester, 2005)
Populus gamblei Dude a southern-most Poplar tree in the Northern Hemisphere, endemic to India from Darjeeling hills, North Bengal, Arunachal Pradesh and Sikkim, has now been reported from wild for the first time from Nagaland. A tree of about 15 m high and girth of 3.2 m has also been measured in Nagaland. About 40 small or medium sized trees were also located in the area. Twenty four hours dip treatment of branch cutting in aqueous solution of 200 hours ppm concentration of Indole Acetic gives 70% roo.ting. It is used by local people of Nagaland for construction temporary huts in shifting cultivated areas. In Kalimpong hills, West Bengal it is locally called 'Sungrikong' (Lepcha) and 'Pipalpati' or 'Pipile' (Nepalese).